Profiling of Tumor Cell‐Delivered Exosome by Surface Enhanced Raman Spectroscopy‐Based Biosensor for Evaluation of Nasopharyngeal Cancer Radioresistance (Adv. Healthcare Mater. 8/2023). Issue 8 (24th March 2023) - Wu, Qiong; Ding, Qin; Lin, Wanzun; Weng, Youliang; Feng, Shangyuan; Chen, Rong; Chen, Chuanben; Qiu, Sufang; Lin, Duo
Abstract : Surface‐Enhanced Raman Spectroscopy In article 2202482 by Chuanben Chen, Sufang Qiu, Duo Lin and co‐workers, the molecular profiles of radioresistant nasopharyngeal cancer (NPC) cell‐derived exosomes are characterized by a surface‐enhanced Raman spectroscopy platform integrated with proteomics. Using the deep learning‐based diagnostic model, the radioresistance‐related exosomes can be identified well. These findings show the promising potential of exosomes as a novel biomarker for the evaluation of NPC radioresistance.